Determinants of STI/HIV stigma and communication management among heterosexual couples in Kenya. Issue 2 (4th March 2022) - Sharma, Bonita B.; Small, Eusebius; Nikolova, Silviya Pavlova
ABSTRACT: Communication of sexually transmitted infections (STI) and Human Immunodeficiency Virus (HIV)/AIDS serostatus can motivate people to get tested and receive care, while also risk being stigmatized. Using the communication management theory, this study used the Demographic and Health Surveys (DHS) - Kenya (2014/2015) to assess factors influencing the willingness of 5265 married or cohabitating Kenyan couples to communicate their STI and serostatus. Chi-square and logistic regression models show women are more likely to inform their partner about being tested for HIV [ χ 2 (1) = 4.511 p  < 0.05]; they are also more willing to care for relatives with HIV [ χ 2 (2)=12.488, p  < 0.01], and are more protective of serostatus information boundaries. The findings suggest that men and women manage their STI and HIV communication differently. Understanding gender differences in sexual health communication management can better help health practitioners assist in treatment-adherence and prevention. More in-depth studies and structural understandings of communication of HIV/STI are recommended.